Biochemical and pathological findings of pregnancy toxemia in Saanen doe: A case report - Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Chung, Eric Lim Teik; Sadiq, Muhammad Abubakar; Mohammed, Konto; Osman, Abdinasir Yusuf; Rahmat, Nurakmaliah binti Rahamat; Razak, Ismasyahir Abdul; Lila, Mohd Azmi Mohd; Haron, Abdul Wahid; Saharee, Abdul Aziz (Journal of Advanced Veterinary and Animal Research, 2015)
A pregnant Saanen doe aging 1.5-year and weighing 40 kg was presented to the Large Animal Unit of Universiti Putra Malaysia Veterinary Hospital with history of inability to stand up. Transabdominal ultrasonography of the animal revealed two live fetuses at late pregnancy. Blood examination revealed decreased lymphocyte numbers, and increased monocytes count. Biochemical analyses showed marked decrease in glucose level and elevated level of aspartate aminotransferase (AST) and creatine kinase (CK). The goat was administered with 200 mL 20% Dextrose (G-20), NaCl solution (at 1.3 mL/animal), Flunixine meglumine (at 2.2 mg/kg bwt), and Vitavet multivitamin (at 1 mL/10 kg bwt). The prognosis of the case was grave, and the goat was sacrificed in order to save the fetuses. However, the fetuses were died within 10 min. Necropsy of the doe showed pale, yellow and friable liver and congested lungs, while histopathological evaluation of the liver showed diffuse hepatic lipidosis. Pregnancy toxemia in doe can be prevented by providing proper nutrition. http://dx.doi.org/10.5455/javar.2015.b78